PENGARUH MODEL PEMBELAJARAN SAVI (SOMATIC, AUDITORY, VISUAL, INTELECTUALLY) TERHADAP MOTIVASI DAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SDN TANJUNG KEDIRI TAHUN AJARAN 2023/2024 - Churiatunn’Adhia, Churiatunn’Adhia; Pratiwi, Emy Yunita Rahma (Prodi Pendidikan Guru Sekolah Dasar, 2024)
The research was motivated by the lack of student motivation to learn in mathematics subjects which affected student learning outcomes, especially in class IV at SDN Tanjung Kediri. The purpose of this research is to determine the effect of using the SAVI (Somatic, Auditory, Visual, Intellectually) learning model on the motivation and learning outcomes of class IV students at SDN Tanjung Kediri. This research used a mixed method approach and the type of research used was explanatory design with. This research was conducted at SDN Tanjung, Pagu District, Kediri Regency with the sample used being twenty-seven fourth grade students. In this research, the data collection methods are in the form of giving questionnaires, giving questions or tests, interviews, observation and documentation. The results of the research show that there is a significant and positive influence on the development of student motivation and learning outcomes, where student motivation increases further with the use of the SAVI learning model, which is further strengthened by the results of interviews and observations when learning is carried out.